Methods of Working with Animations in the Scratch Program (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The modern stage of educational reforms promotes urgent tasks related to the rapidity of changes taking place in society, faster adaptation to new and higher demands placed on educational institutions.